(untitled) (Nepalese Journal of Hospitality and Tourism Management, 2020)
This paper examines the relationships between the knowledge management enablers and knowledge creation externalisation in the hospitality industry such as hotel, travel and trekking agencies in Nepal. The study is based on primary data with 382 responses. The self-administered questionnaires were used to collect the perceptive opinions from the respondents. The study concludes that the key knowledge management enablers such as collaboration, trust, learning, centralisation and information technology do influence to the knowledge creation externalisation positively. Managers should promote collaboration, trust, learning and information technology facilities for employees to create knowledge in organisation.